Pengaruh Kepemimpinan Kepala Sekolah dan Disiplin Guru terhadap Kinerja Guru - Irfiana, Fuadiyah; Siswanto, Romi (Academy of Education Journal, 2024)
This research aims to: 1) determine whether or not there is an influence of school principal leadership on teacher performance; 2) knowing whether or not there is an influence of teacher discipline on teacher performance; 3) determine whether or not there is an influence of the principal's leadership and teacher discipline on teacher performance. The research method used is a quantitative method. The results of this research show that: 1) there is a very significant positive influence between the principal's leadership style on teacher performance; 2) there is a very significant positive influence between job satisfaction and teacher performance; 3) there is a positive influence between organizational commitment and job satisfaction together on teacher performance.